DAMPAK PENGELOLAAN OBJEK WISATA BUKIT KASIH PADA PENDAPATAN MASYARAKAT DI DESA KANONANG EMPAT KECAMATAN KAWANGKOAN BARAT KABUPATEN MINAHASA - PAENDONG, FERO CHRISTANIA; POSUMAH, JOHNNY HANNY; MAMBO, RULLY (JURNAL ADMINISTRASI PUBLIK, 2022)
The purpose of this study was to determine the Impact of Management of Bukit Kasih Tourism Object on Community Income. This research is a descriptive qualitative research. Bukit Kasih is one of the well-known tourist attractions in North Sulawesi Province and many tourists have come to visit both from outside the region and from foreign countries. Tourism management aims to provide benefits for preservation and utilization of tourism potential, especially in the Bukit Kasih tourist attraction. Tourism management provides direct benefits to the community, both in the form of positive and negative impacts. The positive impact felt by the people of Kanonang Empat Village is the opening of business opportunities so as to reduce unemployment in Kanonang Empat Village so as to improve the welfare of the community. The negative impact of the management of the Bukit Kasih tourist attraction is that there is a lot of agricultural land that is not cultivated by the community because people prefer to work and work at the Bukit Kasih tourist attraction which results in a decrease in food yields. It is hoped that the Bukit Kasih Tourism Object can continue to be developed so that it can attract more tourists so that it can provide more job opportunities for the people of Kanonang Empat Village Â  Keywords: Impact, Management, Tourism Object, Community Income Â 